DEVELOPMENT OF THE OPERATING MODEL OF INTRADEPARTAMENTAL PLANNING SYSTEM - A. V. Zvontsov; I. G. Fomina (Дискурс, 2018)
The main purpose of operations management of production activities of the enterprise is primarily to ensure the effective implementation of a continuous production process. One of the mechanisms of organizing and managing production tasks is the system of internal planning of production, which meets the requirements of organizing coordinated and integrated work of all production areas of the shop to manufacture a given range of products in the established volumes and terms with the most efficient use of all production resources. The article describes the features of the development of the internal planning system operating model, the order of work and the requirements for its implementation, considering the possibility of tasks automation.